70-Gb/s amplitude-shift-keyed system with 10-GHz clock recovery circuit using duty cycle division multiplexing - Amouzad Mahdiraji, G.; Abdullah, M.K.; Mokhtar, M.; Mohammadi, A.M.; Abas, A.F.; Basir, S.M.; Abdullah, R.S.A.R. (Photonic Network Communications, 2009)
The performance of ASK over DCDM for up to seven channels is reported. The aggregate bit rate of 70 Gb/s is achieved with only 160-GHz modulation bandwidth. The clock and data recovery are realized at 10-GHz clock rate, which is very economic and efficient. At 7 Ã 10 Gb/s, the worst receiver sensitivity ofâ10 dBm, OSNR of 41.5 dB and chromatic dispersion tolerance of Â±17 ps/nm are achieved. Whereas, for the best channel, the receiver sensitivity,OSNR, and chromatic dispersion tolerance are â23.5dBm, 29dB, and Â±36 ps/nm, respectively.